Applied mineralogy applications in industry and environment - Mukherjee, Swapna (Springer Capital Publishing Co., 2011)
This book covers the entire spectrum of mineralogy and consolidates its applications in different fields. Part I starts with the very basic concept of mineralogy describing in detail the implications of the various aspects of mineral chemistry, crystallographic structures and their effects producing different mineral properties. Part II of the book describes different aspects of mineralogy like geothermobarometry, mineral thermodynamics and phase diagrams, mineral exploration and analysis, and marine minerals. Finally Part III handles the applications in industrial, medicinal and environmental mineralogy along with precious and semiprecious stone studies. The various analytical techniques and their significance in handling specific types of mineralogical problems are also co